The performance of Nafion (R) 424 in the membrane electrolysis of borax solution - (:unkn) unknown (ELSEVIER SCIENCE INC, 2012)
The aim of the study was to investigate the performance of a monolayer cation exchange membrane (Nafion (R) 424) in the membrane electrolysis of aqueous borax solution. Membrane cell was basically composed of a hydrogen evolving cathode, oxygen evolving anode and Nafion (R) 424. Boric acid solution, sodium hydroxide solution, oxygen and hydrogen gases were produced by continuous electrolysis process. The effects of different catholyte concentrations (10, 20, 30 and 35% NaOH) on the current efficiency were investigated. The electrical power consumption per ton for the production of sodium hydroxide (100%) and boric acid were calculated and the qualities of boric acid products were determined. (C) 2012 The Korean Society of industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Membrane electrolysis; Borax; Boric acid; Sodium hydroxide, Nafion (R) 424; SYSTEM; WATER